Determinants of Indonesia frozen yellowfin tuna exports to main destination countries - Zain, Zainuri Syam; Vivi Silvia,; Taufiq C. Dawood , (Technium Social Sciences Journal, 2021)
Frozen yellowfin tuna is the type of tuna product that Indonesia exports the most to the global market in 2010 – 2019. The export volume of Indonesian frozen yellowfin tuna to main destination countries in 2010 – 2019 fluctuated. The purpose of this study was to determine and analyze the effect of export prices, exchange rates, GDP per capita, and economic distance on Indonesian frozen yellowfin tuna exports to main destination countries. The data in this study is panel data which is a combination of time series data for 2010 – 2019 and cross-section data for 6 countries. The best model to analyze this research is the Fixed Effects Model. The results showed that export prices and exchange rates had a negative and significant effect on Indonesian frozen yellowfin tuna exports to the main destination countries, while GDP per capita had a positive effect on Indonesian frozen yellowfin tuna exports to the main destination countries. The results also show that economic distance does not affect Indonesia's frozen yellowfin tuna exports to the main destination countries. Keywords: Export, Frozen Yellowfin Tuna, Panel Data